The Architecture of a Mosque Without a Dome as a Trace of the Development of Muslim Intellectuals - Putri Suryandari (JURNAL INDO-ISLAMIKA, 2021)
The architectural style of the mosque without the dome is becoming a phenomenon in the development of Islamic architecture this decade. The dome, which has been a symbol of Islam for hundreds of years, seems to no longer be the main target of mosque design, both in the world and in Indonesia. Seen by the increasing number of architects who build mosques without domes. What underlies this change? What is the change in thinking or intellectual power of the Muslim community, underlying this change? This study uses descriptive analysis method, namely the analysis process is carried out based on theoretical studies with literature studies, journals, magazines, and observations in the field. The result is, the pattern of Muslim intellectual thought in the Islamic reform era resulted in the Islamization of science, namely, adapting Islamic thought to modern knowledge. This era of Islamic reform, left an imprint on the architectural design of the mosque in accordance with the principles of architectural science and the purification of the philosophy of the mosque of the era of Rasulullah SAW, namely honest, simple, geometric, with little ornamentation and without a dome, and adapted to the local culture.